2016
DOI: 10.5530/srp.2017.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion Micro Emulsion and Nano Emulsion: A Review

Abstract: Lipid dosage forms are attractive delivery systems for hydrophobic drug molecules. Emulsion is one of the popular system since many decades. Pharmaceutical applications of emulsions widened especially after micro and nano-emulsion emergence. This paper is an attempt to summarise comparative aspects like definition, theories, types, methods of preparations, advantages, disadvantages and methods of analysis of emulsion, micro-emulsion and nano-emulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
1
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(206 citation statements)
references
References 36 publications
3
166
1
13
Order By: Relevance
“…The stock emulsions (32 μL/mL; pH 5.6 ± 0.1) of CLEO and CREO were prepared by directly adding EOs in MRS broth (HiMedia) containing Tween 80 (1%, v/v; Sigma–Aldrich, St. Louis, MI, USA) as an emulsifier, followed by vigorous shaking using a vortex for 5 min. Using this method, the prepared emulsions presented droplet sizes characteristic of macroemulsions (Friedman, Henika, & Mandrell, ; Kale & Deore, ). At the assayed concentration (1%, v/v), Tween 80 did not present inhibitory effects against the test strains used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The stock emulsions (32 μL/mL; pH 5.6 ± 0.1) of CLEO and CREO were prepared by directly adding EOs in MRS broth (HiMedia) containing Tween 80 (1%, v/v; Sigma–Aldrich, St. Louis, MI, USA) as an emulsifier, followed by vigorous shaking using a vortex for 5 min. Using this method, the prepared emulsions presented droplet sizes characteristic of macroemulsions (Friedman, Henika, & Mandrell, ; Kale & Deore, ). At the assayed concentration (1%, v/v), Tween 80 did not present inhibitory effects against the test strains used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that the size of nanoemulsion particles tends to decrease with the addition of nanosilver. It could be explained that in the case without nanosilver, surfactant and oil together form a complex film at the oil water interface and thus generate emulsion droplets with hydrophobic tails bunched up, hydrophilic heads pointing towards the water [31]. In addition of nanosilver, nanosilver might be played the role of a hydrophobic core of emulsion droplet and attracted monolayer hydrophobic tails to form smaller nanoemulsion particles.…”
Section: Combination Of Nanoemulsion Based On Essential Oil With Nanomentioning
confidence: 99%
“…Nanoemulsions are transparent dispersions of nanoscale droplets very similar to microemulsions but obtained by different methods. Nanoemulsions are defined as thermodynamically unstable systems produced by mechanical shear in contrast to microemulsions that are thermodynamically stable and form spontaneously [67].…”
Section: Nanoemulsionsmentioning
confidence: 99%